A low cost technology for the cultivation of Ganoderma lucidum - Geetha, D; Suharban, M; Palan, Gokula; Deepa Rani, C V (Mushroom Research, 2012)
Suitability of natural logs and different agricultural wastes viz., paddy straw, paddy chaff, sugarcane bagasse and rubber sawdust was studied for the cultivation of Ganoderma lucidum. Highest yield was obtained from a mixture of paddy chaff (80%), rice bran (20%), Calcium carbonate (2%), followed by rubber sawdust mixture. Paddy straw recorded the lowest yield. The spawn run and primodial formation were earlier (10 days) in paddy chaff based medium followed by rubber sawdust. The highest biological efficiency of 15% was recorded in paddy chaff followed by 12% in rubber sawdust mixture. The spawn run was poor in the paddy straw and only 1 or 2 small primordia were developed. Of the two methods tried, artificial log method resulted in faster spawn run, early sporophore production and higher yield compared to natural log method. Natural log method of cultivation in Breadfruit (Artocarpus altilis) took maximum time for spawn run (25 days) and yield was also low.